2015
DOI: 10.15171/hpp.2015.023
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Violent Toys in Weekly Circulars of Popular Retailers in the United States

Abstract: Background: Violence is a pervasive problem in the United States. Toys, far from trivial playthings, are a reflection of society, including its beliefs and values. The purpose of this study was to describe the extent to which violent toys are marketed in online weekly flyers of popular retailers, how the violence is manifested, and whether violent toys are marketed differentially to boys and girls. Methods: For this cross-sectional observational study, online circulars from 5 major retailers were downloaded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While Ebola infection carries a high risk of death (i.e., about 50%), it is only spread through direct contact with infected bodily fluids (i.e., it is not spread by food, air, or water) (Bell, 2016). Despite Ebola posing little danger to US citizens at that time, extensive media coverage and speculation centered on dread risk fears about an Ebola epidemic in the United States (i.e., strong fears that result from low probability, high consequence events) (Basch et al, 2014;Gigerenzer, 2004). Study 4 was a secondary analysis of a risk communication experiment conducted in October 2014, 3 weeks after the first case of Ebola was confirmed in the United States, the full details of which are reported elsewhere (Petrova, 2016).…”
Section: Studymentioning
confidence: 99%
“…While Ebola infection carries a high risk of death (i.e., about 50%), it is only spread through direct contact with infected bodily fluids (i.e., it is not spread by food, air, or water) (Bell, 2016). Despite Ebola posing little danger to US citizens at that time, extensive media coverage and speculation centered on dread risk fears about an Ebola epidemic in the United States (i.e., strong fears that result from low probability, high consequence events) (Basch et al, 2014;Gigerenzer, 2004). Study 4 was a secondary analysis of a risk communication experiment conducted in October 2014, 3 weeks after the first case of Ebola was confirmed in the United States, the full details of which are reported elsewhere (Petrova, 2016).…”
Section: Studymentioning
confidence: 99%
“…It also made some to flee from isolation centers, and suspicious patients in dire need of medical attention were abandoned (Iddrisu, 2018). Basch et al (2014) investigated how three widely read newspapers covered Ebola in the United States. The study found that the media primarily focused on death tolls, with less emphasis on educating the readers on the critical aspect of the Ebola epidemic.…”
Section: Literature Reviewmentioning
confidence: 99%